THEORETICAL EVALUATION OF THE PERMEABILITY OF DISCHARGE ITEM (LiOOH) IN Li-O-2 BATTERIES - (:unkn) unknown (PLAPIQUI(UNS-CONICET), 2021)
Both lithium ions and protons have been directly implicated in oxygen reduction and evolutionary responses and lithium hydroperoxide and lithium hydroxide are recognized as prevailing discharge ingredients. Attributes of lithium hydroperoxide shall be evaluated in principle. Impressively, the reaction of lithium hydroperoxide to triiodide shows quicker material properties, which allows a slightly lower excessive-potential during the charging cycle. The frontier molecular orbitals (FMOs), UV-Vis, and solvation model-based studies remained unknown. Therefore, we intended to study the Reaction path study, natural bond orbital, FMOs, UV-VIS, thermo-dynamic properties and medium influence on solvation energies, dipole moment, FT-IR and FT-Raman using polarizable continuum model (PCM) and density-based solvation model (SMD). The electronic properties of the molecule were calculated by M06-2X/6-31G (d,P) and B3LYP/6-31G (d,p) level of theories. Natural bond orbital discloses that the optimum stabilization energy managed to reach 39.64 kJ / mol, which is accountable for the extra stability of the compound. Based on materials impacts on FT-IR and FT-Raman intensities are identified in the understudy compound. Frequencies improved from gas to the solvent process.
Keywords: Lithium hydroperoxide; DFT; FMO; UV-Vis; B3LYP/6-31G (d,p); SCHIFF-BASES; COMPLEXES; DFT